GAMBARAN KEBERADAAN BAKTERI STAPHYLOCOCCUS AUREUS, KONDISI LINGKUNGAN FISIK, DAN ANGKA LEMPENG TOTAL DI UDARA RUANG RAWAT INAP RSUD PROF. DR. M.A HANAFIAH SM BATUSANGKAR - Ayu Rahmadani; Budiyono Budiyono; Suhartono Suhartono (Jurnal Kesehatan Masyarakat (Undip), 2017)
The hospital is a place of health services, a gathering place for the sick and healthy people, so it can be a place of disease transmission and health problems. This study aims to determine the description of the presence of Staphylococus aureus bacteria and Total Plate Count of air in the inpatient room of RSUD Prof. DR. M.A Hanafiah SM Batusangkar. This study used cross sectional study design with univariate descriptive analysis, mean difference test and correlation test. The population in this study is inpatient room with 30 samples. The results of this study showed that no bacteria Staphylococcus aureus in air inpatient room and average Total Plate Count in the air 32,07 CFU/m3. Average of air temperature 28,170C, average of air humidity 65,33%, average of lighting intensity 286,99 lux, average of occupancy density 6,77 m2/person, and there were 21 (70%) used air conditioner in the inpatient room. There were significant differences in mean temperature, lighting intensity, and occupancy density in inpatient room with pvalue 0,038, 0,040, and 0,040, no significant difference in moisture average and Total Plate Counts with pvalue 0,796 and 0,650. There is no significant correlation between temperature, humidity, lighting intensity and occupancy density with Total Plate Counts with pvalue 0,078, 0,150, 0,303, and 0,075. In conclution there was no Staphylococcus aureus bacteria and the conditions of temperature, humidity, and lighting intensity in the hospital's inpatient room do not meet the standards that have been determined.